INVESTIGATING PRE-SERVICE MATHEMATICS TEACHERS' PEDAGOGICAL CONTENT KNOWLEDGE OF NUMBER PATTERNS - (:unkn) unknown (INT GRP PSYCHOL MATH EDUC, 2009)
The purpose of this paper is to investigate the development of two pre-service mathematic teachers' pedagogical content knowledge with special attention to students' understanding of and difficulties with finding the rule of number patterns. A case study was conducted to explore this development through a school practicum course and how the observations of number pattern lessons in schools contribute to the knowledge of student difficulties.. The analysis of data indicated that the observation and discussions of number pattern lessons resulted in considerable change in the way pre-service teachers addressed student difficulties in their lessons.